Interfacial concentrations of chloride and bromide in zwitterionic micelles with opposite dipoles: Experimental determination by chemical trapping and a theoretical description - de Souza, Tereza Pereira; Chaimovich, Hernan; Fahr, Alfred; Schweitzer, Bianca; Neto, Augusto Agostinho [UNESP]; Cuccovia, Iolanda Midea (Academic Press Inc. Elsevier B.V., 2012)
Interfacial concentrations of chloride and bromide ions, with Li+, Na+, K+, Rb+, Cs+, trimethylammonium (TMA(+)), Ca2+, and Mg2+ as counterions, were determined by chemical trapping in micelles formed by two zwitterionic surfactants, namely N-hexadecyl-N,N-dimethyl-3-ammonio-1-propanesulfonate (HPS) and hexadecylphosphorylcholine (HDPC) micelles. Appropriate standard curves for the chemical trapping method were obtained by measuring the product yields of chloride and bromide salts with 2,4,6-trimethyl-benzenediazonium (BF4) in the presence of low molecular analogs (N,N,N-trimethyl-propane sulfonate and methyl-phosphorylcholine) of the employed surfactants. The experimentally determined values for the local Br- (Cl-) concentrations were modeled by fully integrated non-linear Poisson Boltzmann equations. The best fits to all experimental data were obtained by considering that ions at the interface are not fixed at an adsorption site but are free to move in the interfacial plane. In addition, the calculation of ion distribution allowed the estimation of the degree of ion coverage by using standard chemical potential differences accounting for ion specificity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ionic selectivity; Chemical trapping; Zwitterionic micelles; Poisson-Boltzmann